The TanDEM-X 30m Edited DEM Released for Scientific Use - Gonzalez, Carolina; Bueso Bello, Jose Luis; Bachmann, Markus; Rizzoli, Paola (2024)
The TanDEM-X twin satellites have been acquiring bistatic SAR data for 13 years. The main mission goal was achieved in 2016: the generation of a global DEM of unprecedented homogeneous quality and resolution. For the processing of the second global DEM, the TanDEM-X DEM 2020, a gapfree DEM was required. Therefore, we developed a fully automated edition to fill the gaps corresponding to about 0.1% of the land mass and to flatten the water bodies. External reference DEM datasets were used to fill the gaps. The Reference Elevation Model of Antarctica (REMA) was used for editing the Antarctic continent. Here we found large overlapping gaps within both REMA DEM and the TanDEM-X DEM. We developed a new algorithm to patch these regions in the REMA DEM in order to edit the TanDEM-X DEM with a single editing approach. This method considers the recursive calibration of new InSAR-derived DEMs in a mosaicking process. In this paper we present the fully automatic editing approach used for the released version of the TanDEM-X 30m Edited DEM, the challenges faced and the future activities related to this topic.